Optimization Of Marriage Registration To Realize Legal Certainty And Civil Rights Protection - Indra Krestianto (Jurnal Impresi Indonesia, 2025)
Marriage has an important role in shaping families and community life. In Indonesia, Law Number 1 of 1974 has stipulated that marriage registration must be carried out to ensure legal certainty and protection of civil rights such as maintenance rights, inheritance rights, and rights to common property. This study aims to analyze the legal politics of marriage registration, the legal impact of registered and unregistered marriages, and offer an ideal form of fair and useful registration. The research method used is normative law with a legislative approach. The results of the study show that marriage registration is not only administrative, but also important for the certainty of family legal status. Optimizing recording through regulatory reform and public education is needed to strengthen legal protection in Indonesia.